(untitled) - Robin, Corey; Corey Robin (Oxford,New York, 2004)
For many commentators, September 11 inaugurated a new era of fear. But as Corey Robin shows in his unsettling tour of the Western imagination--the first intellectual history of its kind--fear has shaped our politics and culture since time immemorial
Keywords: Political science; Fear